PENERAPAN STRATEGI THINK-TALK-WRITE DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII4 SMP NEGERI 3 PEKANBARU - Yosi Putri; Syofni '; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and increase the student’s mathematics learning outcomes through the implementation of the Think-Talk-Write Strategy in Cooperative Learning. This type of research is the Classroom Action Research with two cycle. The research was conducted in class VII4 SMPN 3Pekanbaru in the second semester of the 2015/2016 academic year with the subject of as many as 38 students, consist of 21 boys and 17 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. Data analysis technique used is descriptive statistical analysis. Based on the result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 13 person (34,2%), 16 person (42,1%) and 28 person (73,68%). Results of this research indicates that application of the Think-Talk-Write Strategy in Cooperative Learning can improve learning process and increase mathematics learning outcomes from the students at class VII4 SMPN 3Pekanbaru in the second semester academic years 2015/2016 at Basic Competencies 6.2 Identify the properties of a rectangle, square, trapezoid, parallelogram, rhombus and kite and Basic Competencies 6.3 Calculate the circumference and area woke triangles and squares as well as use them in problem solving.Keywords: Cooperative Learning, Think-Talk-Write Strategy, Learning Process, student’s mathematics learning outcomes, Classroom Action Research.